J.M. Coetzee : South Africa and the politics of writing - Attwell, David (Perspectives on Southern Africa ;, 1993)
David Attwell defends the literary and political integrity of the South African novelist J.M. Coetzee, arguing that he has absorbed the textual turn of postmodern culture while still addressing his nation's ethical crisis. As a form of "situational metafiction," Coetzee's novels are shown to reconstruct and critique some of the key discourses in the history of colonialism and apartheid from the eighteenth century to the present. While self-conscious about fiction-making, Coetzee's work takes seriously the condition of the society in which it is produced. Attwell begins by describing the intellectual and political contexts of Coetzee's fiction. He proceeds with a developmental analysis of the corpus of six novels, drawing on Coetzee's other writings in stylistics, literary criticism, translation, political journalism, and popular culture. Attwell's elegantly written analysis deals both with Coetzee's subversion of the dominant culture around him and with his ability to grasp the complexities of giving voice to the anguish of South Africa